2014
DOI: 10.1007/s00253-014-5671-1
|View full text |Cite
|
Sign up to set email alerts
|

High-cell-density cultivation of recombinant Escherichia coli, purification and characterization of a self-sufficient biosynthetic octane ω-hydroxylase

Abstract: We have recently described the biocatalytic characterization of a self-sufficent biosynthetic alkane hydroxylase based on CYP153A13a from Alcanivorax borkumensis SK2 (thereafter A13-Red). Despite remarkable regio- and chemo-selectivity, A13-Red suffers of a difficult-to-reproduce expression and moderate operational stability. In this study, we focused our efforts on the production of A13-Red using high-cell-density cultivation (HCDC) of recombinant Escherichia coli. We achieved 455 mg (5,000 nmol) of functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Compared with CYP153A33 (50 nmol/g cdw ), the expression level of CYP153A13 was only 11 nmol/g cdw (Table S4). Similarly, the expression level of selfsufficient CYP153A13-Red was only 10 % as that of CYP102A1 (i.e., BM3) in E. coli BL21 (DE3), which is well known for its high soluble expression (Bordeaux et al 2014), indicating that in solublization and functional expression of CYP153A13, it would be critical to achieve high product yields, becoming a big challenge for application in industry. Although the CYP153A35 from G. alkanivorans was not yet characterized as ω-hydroxylase, G. alkanivorans strain was identified as indigenous diesel-degrading strain (Young et al 2005), and three alkanal monooxygenase genes related to hydrocarbon degradation were suggested by genome sequencing (Wang et al 2014), suggesting that CYP153A35 is very likely to show ω-hydroxylation activity toward fatty acids.…”
Section: Discussionmentioning
confidence: 98%
“…Compared with CYP153A33 (50 nmol/g cdw ), the expression level of CYP153A13 was only 11 nmol/g cdw (Table S4). Similarly, the expression level of selfsufficient CYP153A13-Red was only 10 % as that of CYP102A1 (i.e., BM3) in E. coli BL21 (DE3), which is well known for its high soluble expression (Bordeaux et al 2014), indicating that in solublization and functional expression of CYP153A13, it would be critical to achieve high product yields, becoming a big challenge for application in industry. Although the CYP153A35 from G. alkanivorans was not yet characterized as ω-hydroxylase, G. alkanivorans strain was identified as indigenous diesel-degrading strain (Young et al 2005), and three alkanal monooxygenase genes related to hydrocarbon degradation were suggested by genome sequencing (Wang et al 2014), suggesting that CYP153A35 is very likely to show ω-hydroxylation activity toward fatty acids.…”
Section: Discussionmentioning
confidence: 98%
“…To date, most studies have focused on the creation of self-sufficient CYP153s and WC (or permeabilized WC) biotransformations, with very few studies performed using CYP153s in vitro or as purified enzymes. Activity and stability of the self-sufficient CYP153A13RhFRed were shown to be improved through the addition of BSA and catalase [25]. Since we have observed that using CFE instead of purified enzymes led to significantly higher final product concentrations, we revisited the influence of BSA and catalase as well as CFE on the activity and stability of CYP153 biotransformations.…”
Section: Discussionmentioning
confidence: 99%
“…Purified biocatalysts were used in a 1:1:6 (CYP153A6:FdR:Fdx) molar ratio as previous investigation have indicated that Fdx concentration can significantly influence product yields [15,22]. Bovine serum albumin (BSA) and catalase have been shown to improve the stability of reactions using purified CYP153A13RhfRed [25] and were included in the reaction mixture to final concentrations of 10 mg mL −1 and 0.5 U mL −1 , respectively. Glucose dehydrogenase (GDH) was selected as cofactor regeneration system as it can accept both NAD + and NADP + with similar turnover frequencies [26,27].…”
Section: Cofactor Regeneration Using Glucose Dehydrogenasementioning
confidence: 99%
“…Considered over extended periods, the use of Triton X-100 has led to mixed results in the literature, with Grant et al reporting a positive effect on the oxidation of dodecane in microwells and shake flasks when Triton X-100 was present [ 19 ], while Julsing et al found that Triton X-100 was not helpful in the oxidation of fatty acid methyl esters [ 18 ]. Bordeaux et al found that Triton X-100 was moderately helpful in octane bioconversions when the organic phase included a co-solvent, but that the surfactant suppressed turnovers considerably when the organic phase consisted of pure octane [ 34 ]. Julsing et al also used pure substrate as the organic phase, while Grant et al had dimethylsulfoxide (DMSO) present in the organic phase, and found that the beneficial effects of Triton X-100 were enhanced when more DMSO was present.…”
Section: Resultsmentioning
confidence: 99%